Exploring oxidative stress and endothelial dysfunction as a mechanism linking bisphenol S exposure to vascular disease in human umbilical vein endothelial cells and a mouse model of postnatal exposure. (December 2022) - Easson, Sarah; Singh, Radha Dutt; Connors, Liam; Scheidl, Taylor; Baker, Larissa; Jadli, Anshul; Zhu, Hai-Lei; Thompson, Jennifer
Abstract: Background: Structural analogues used to replace bisphenol A (BPA) since the introduction of new regulatory restrictions are considered emerging environmental toxicants and remain understudied with respect to their biological actions and health effects. Studies reveal a link between BPA exposure and vascular disease in human populations, whereas the vascular effects of BPA substitutes remain largely unknown. Objectives: To determine the effect of BPS, a commonly used BPA substitute, on redox balance, nitric oxide (NO) availability and microvascular NO-dependent dilation. Methods: In human umbilical vein endothelial cells (HUVEC), production of reactive oxygen species (ROS) and NO after exposure to BPS was measured using fluorescent probes for DCFDA and DAF-FM diacetate, respectively. The contribution of endothelial NO synthase (eNOS) uncoupling to ROS generation was determined by measuring ROS in the presence or absence of an eNOS inhibitor (L-NAME) or eNOS co-factor, BH4, while the contribution of mitochondria-derived ROS was determined by treating cells with mitochondria-specific antioxidants prior to BPS exposure. Bioenergetic profiles were assessed using Seahorse extracellular flux analysis and mitochondria membrane polarization was measured with TMRE and JC-1 assays. In a mouse model of low dose BPS exposure, NO-mediated endothelial function was assessed in pressurized microvessels by inducing endothelium-dependent dilation in the presence or absence of L-NAME. Results: BPS exposure (≥25 nM) reduced NO and increased ROS production in HUVEC, the latter corrected by treating cells with L-NAME or BH4. BPS exposure led to a loss of mitochondria membrane potential but had no impact on bioenergetic parameters except for a decrease in the spare respiratory capacity. Treatment of HUVEC with mitochondria-specific antioxidants abolished the effect of BPS on NO and ROS. NO-mediated vasodilation was impaired in male mice exposed to BPS. Discussion: Exposure to BPS may promote cardiovascular disease by perturbing NO-mediated vascular homeostasis through the induction of oxidative stress.